CORPORATE CULTURE IN THE SYSTEM OF STRATEGIC DEVELOPMENT OF ENTREPRENEURIAL ENTITIES (Development Service Industry Management, 2025)
It is proven that in the current conditions of high competition, rapid transformations of the market environment, and growing requirements for management efficiency, corporate culture is one of the key intangible factors of the successful functioning of business entities. It shapes the values, management style, motivational climate and level of team cohesion, directly affecting organizations' sustainability and competitiveness. At the same time, in domestic practice, strategic management of corporate culture remains insufficiently developed, which significantly limits its potential as a resource for long-term business development. The article provides a theoretical generalization of approaches to forming corporate culture as a component of the strategic development of business structures. The author analyzes modern research covering a wide range of issues: from disclosing the essence and typology of corporate culture to its role in shaping adaptability, innovation and ethical environment in organizations. It is found that the key areas are the integration of corporate culture into the strategy of enterprises, its impact on human resources management and transformation under the influence of external challenges and innovations. A systematic approach to forming corporate culture, which includes five stages, is substantiated: Analytical and diagnostic stage, conceptual and target stage, strategic and planning stage, implementation stage, and control and correction stage. The proposed model ensures the adaptability and systematic nature of the process of corporate culture development, which is the key to sustainable strategic growth. It is substantiated that corporate culture is a vital strategic resource that determines the level of adaptability and competitiveness of enterprises. The need for further research on the development of methods for quantifying the impact of corporate culture on performance, as well as practical models of its transformation in the context of digitalization and globalization challenges, is highlighted.
Keywords: corporate culture; strategic development; entrepreneurial entities; motivation; adaptability; competitiveness; personnel management